Quality, Storage Stability, and Effect of Cryoprotectants onUltrastructure of Superchilled Chicken - Banerjee, Rituparna; Maheswarappa, Naveena B; Muthukumar , M; Dasoju, Sowmya (Journal of Meat Science, 2024)
The concept of superchilling, an alternative to traditional chilling and  freezing methods, is to reduce the temperature 1-2 °C below the initial  freezing point of the food enabling safe, and high-quality product. This  work was aimed to explore the effects of superchilling (-2±0.5°C), chilling  (4±1°C), and freezing (−18±1°C) on the quality and storage stability of  dressed chicken and also to evaluate the role of cryoprotectants during  superchilling for enhanced meat quality. In superchilled samples,  improved water holding capacity (WHC) and lower shear force values  were observed relative to frozen chicken. SDS-PAGE analysis revealed  the appearance of 29 kDa protein bands in superchilled samples on  7th and 14th day, indicating troponin degradation and tenderization.  Scanning electron microscopy (SEM) studies indicated minimal damage  to muscle fibre ultrastructure in superchilled chicken relative to frozen  samples. Integrity of fibre structure was well maintained in superchilled  samples treated with sorbitol as a cryoprotectant relative to sucrose and  polyphosphate. Results demonstrated the potential use of superchilling  process along with cryoprotectants for improved quality and enhanced  shelf-life of chicken.
Keywords: Superchilling; Chicken meat; Shelf-life; SDS-PAGE; Cryoprotectants; Ultrastructure